Phytochemical profile and anti-allergy properties of Clinacanthus nutans (Burm.F) Lindau extract revealed by ¹1H-NMR-based metabolomics - Khoo, Leng Wei (2018)
Food allergy is an abnormal immunological response arises when a person's immune system wrongly interprets a food as a harmful foreign invader. Although the existing synthetic derived anti-allergy drugs provide effective treatment, the possible side effects on human have drawn the researchers’ attention to seek alternatives from nature source. The present study aimed to profile the metabolites and investigate the pharmacological potency of Clinacanthus nutans, a local traditional herb and vegetable, in managing food allergy using proton nuclear magnetic resonance (1HNMR) metabolomics approach. The first and second parts of the study focused on evaluating the effect of different plant parts, dryings, binary extraction solvent system (ethanol: water ratio) and extraction methods on the phytochemical composition and bioactivity of the plant using metabolomics approach. Subsequently, the optimised plant extract was assessed for its acute toxicity effect on Sprague Dawley rats at a single oral dose of 5000 mg/kg body weight (BW) using both conventional (visual behavioural observation, hematological and biochemical tests) and advanced (serumurinary 1H-NMR metabolomics) toxicity evaluation methods. The optimal plant extract was further evaluated for its anti-allergy effect in a dose dependent manner (125, 500 and 2000 mg/kg BW rat) using in vivo ovalbumin induced active systemic anaphylaxis (OVA-ASA) rat model. From the experiment, water-sonication prepared C. nutans air dried leaf was determined as the optimal extract as it had the highest TPC (51.44 ± 0.63 mg GAE/g of extract) and exhibited the best NO inhibitory activity (IC50: 190.43 ± 12.26 μg/mL) without adverse effect on the RAW cell viability. The analysis further suggested the potential NO inhibitors in the extract were clinacoside A and B, clinamide A, B and C, phytosterols, lupeol, orientin, isoorientin, valine, alanine, acetic acid, and lactic acid. The acute toxicity test showed that the extract-treated rats behaved normal with no observed morbidity, mortality or apparent signs of toxicity. Therefore, the LD50 of C. nutans extract is likely to be above 5000 mg/kg BW. Consequently, the anti-allergy properties of the optimal C. nutans extract was evaluated. A stronger positive correlation of the high dose extract-treated group (2000 mg/kg BW) with the normal group than with the ovalbumin-induced group was observed. The metabolic pathway further suggested the anti-allergy effect of C. nutans may be ascribed to its ability in modulating the carbohydrate metabolism, energy metabolism, lipid metabolism, amino acid metabolism and nucleotide metabolism of sensitised rats. This study is the first report on the potency of C. nutans as an antiallergy agent. The finding of this study therefore, paves a new way for future functional food or drug development in mitigating allergy reaction and lays the basis for any metabolomics related study.